2018
DOI: 10.1111/hepr.13203
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological investigation of steatohepatitic hepatocellular carcinoma: A multicenter study using immunohistochemical analysis of adenoma‐related markers

Abstract: We confirmed that SH-HCC was strongly associated with MS and NAFLD, and found that classification markers of inflammatory HCA were significantly higher in SH-HCC. Further studies are needed to elucidate the relationship between SH-CCC and HCA for understanding the carcinogenic pathways in these diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 40 publications
5
50
1
Order By: Relevance
“…One possibility is steatohepatitic HCC (SH‐HCC). Taniai et al . reported that SH‐HCC was strongly associated with metabolic syndrome and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is steatohepatitic HCC (SH‐HCC). Taniai et al . reported that SH‐HCC was strongly associated with metabolic syndrome and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is steatohepatitic HCC (SH-HCC). Taniai et al 15 reported that SH-HCC was strongly associated with metabolic syndrome and NAFLD. The characteristic features of SH-HCC compared with non SH-HCC are the development of non-cirrhotic liver and larger main tumors with no difference in the rates of solitary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…There has been an increase of reports about HCC in patients with NAFLD/NASH. 37 - 48 As with other liver diseases, the most important risk factors for HCC are cirrhosis, age and male sex. In addition, obesity, type 2 diabetes, and PNPLA3 increase the risk of HCC.…”
Section: Epidemiologymentioning
confidence: 99%
“…On the immunohistochemical phenotype, C reactive protein (CRP) expression was frequent [8] . Immunohistochemical expression of serum amyloid A and CRP was significantly higher in this subtype than conventional HCC as revealed by another study [16] . It was also found that the cancer-associated fibroblasts in SH-HCC more frequently expressed senescence-associated secretory phenotype by immunohistochemical staining [14] .…”
Section: Sh-hccmentioning
confidence: 57%